The Iran-Iraq conflict : recent developments in the international law of naval engagements - Orford, Toby Michael (Institute of Marine and Environmental Law, 2023)
Initial advances into Iranian territory were repulsed and by 1982 Iraq had withdrawn to previously recognised international boundaries. The war on land lapsed into statement with neither side being capable of launching a sufficiently strong offensive to terminate hostilities. Partly in retaliation for Iran's successful blockade of Iraqi shipping and partly in an attempt to cripple Iranian oil exports and undermine the enemy war effort, Iraq expanded the conflict onto the waters of the Persian Gulf. Exclusion zones were declared in the northern Gulf, and shipping calling at the Iranian oil terminal at Kharg Island singled out for unannounced missile attacks. Iraq has hit over 170 tankers in the Gulf war. Iran has made fewer attacks but most of these have occurred outside both the Iranian and Iraqi war zones. Neutral shipping calling at neutral Gulf ports are considered lawful targets for destruction. Recently Kuwaiti-bound' vessels have been hit. Neutral merchant shipping is being stopped and searched at the entrance to the Gulf. The United States, having committed itself to upholding the freedom of neutral navigation in the region, has transferred Kuwaiti tankers to US registration and is escorting the re-flagged vessels to protect them from Iranian interference and attack. The United Nations Security Council has passed Resolutions calling for an end to the hostilities and has denounced attacks on neutral shipping in international waters. No Chapter Vll procedures for collective security enforcement under the Charter have been invoked 6. and not one of the Resolutions is binding.